The mutational landscape of genetic cholestatic diseases in Pakistani children - Cheema, Huma Arshad; Waheed, Nadia; Anjum Saeed; Anjum, Muhammad Nadeem; Fayyaz, Zafar; Ijaz, Sadaqat (Journal of the Pakistan Medical Association, 2023)
Objective: To report the mutational landscape of a clinically diagnosed cohort of paediatric patients with cholestasis liver diseases. Method: The retrospective study was conducted at the University of Child Health Sciences, The Children Hospital, Lahore, Pakistan, from December 10, 2021, to March 31, 2022, and comprised data collected from the Paediatric Gastroenterology and Hepatology unit on demographics, clinical and laboratory findings related to children of either gender aged <12 years and diagnosed with cholestatic liver disease from July 2018 to June 2021. The diagnosis was based on clinical and biochemical findings, with no evidence of biliary atresia and metabolic liver disease. Molecular characterisation was done through whole exome sequencing. Results: Of the 171 children evaluated, 92(53.8%) were diagnosed with genetic cholestatic disorders. There were 52(56%) boys and 41(44%) girls. The median age at presentation was 19.5 months (interquartile range: 51 months). Consanguinity was found in 82(88.1%) cases, and positive family history with one or more affected siblings was noted in 60(64.5%). Exome sequencing identified pathogenic mutations in 13 genes underlying the hereditary cholestasis; ATP8B1, ABCB11, ABCB4, TJP2, NR1H4, DCDC2, ACOX2, AKR1D1, HSD3B7, ABCC2, USP53, SLC10A1, and SLC51A. Of the 70 variants identified, 50(71.4%) were novel variants. The ABCB11-related hereditary cholestasis was the most frequent 27(29%), followed by ABCB4 (26(27.9%). Homozygosity was frequently seen in all except 8(8.6%) children, who had compound heterozygous pathogenic variants. There was no evidence of phenotypic expression in the carrier parents despite the severe nature of the respective mutations identified in the patients. Conclusions: Genetic heterogeneity of paediatric intrahepatic cholestasis showed recurrent and novel mutations. Key Words: Cholestasis, Progressive familial intrahepatic cholestasis, Neonatal sclerosing cholangitis, Genetic mutation, USP53, Bile acid synthetic defects, CLD.